Under Pressure: A Laboratory Investigation into the Effects of Mechanical Loading on Charred Organic Matter in Archaeological Sites. (3rd April 2015) - Ngan-Tillard, Dominique; Dijkstra, Jelke; Verwaal, Wim; Mulder, Arno; Huisman, Hans (D.J.); Müller, Axel
Abstract : The present publication investigates what happens to archaeological sites when they are built over. Focus is put on the degradation of charred organic materials by static loading. It is assumed that materials lose archaeological value if their fragments become too small to be recovered, or too distorted to be classified at species level. Several charred ecofacts of a few millimetres in size (wood fragments, hazelnut shells, and seeds) have been selected and subjected to individual particle strength tests. Assemblages of these particles have also been compressed one-dimensionally and scanned at several stages of testing using laboratory based X-ray microtomography. Microscopic damage by splitting or crushing is found to be limited at the macroscopic yield stress. It initiated at stresses less than 80 kPa for the weakest assemblages, and in all cases at stresses below 320 kPa. (80 kPa represents the load of a 6 m high sand embankment on soft soil that has half-settled underneath the groundwater table, while 320 kPa corresponds to stresses applied beneath the pile foundation level of high-rise buildings.) Sand seeded with charred particles has also been tested to illustrate the beneficial effect of embedment of charred particles in sand during static one dimensional loading.